Pengaruh Spiritual Emotional Freedom Technique (SEFT) terhadap Tekanan darah pada Lansia dengan Hipertensi - Aminatun Indah Kumalasari; Riyani Wulandari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The global elderly population (>60 years) has reached 1.4 billion, with a high vulnerability to cardiovascular disease, including hypertension, which affects approximately 1.28 billion individuals worldwide. Hypertension in the elderly is often chronic and requires long-term management, both pharmacological and non-pharmacological approaches. While antihypertensive medications have proven effective, long-term side effects can include kidney disorders, electrolyte imbalances, and decreased quality of life due to drug dependence. Therefore, the development of non-invasive, affordable, and low-risk alternative interventions is crucial. One non-pharmacological approach currently being studied is the Spiritual Emotional Freedom Technique (SEFT), an emotional healing method that combines spiritual elements, positive affirmations, and stimulation of the body's meridian points. SEFT works through the autonomic nervous system and is believed to reduce psychological stress that contributes to high blood pressure. This therapy is easy to learn, can be performed independently, and does not require special equipment, making it highly suitable for use in elderly communities with limited access to advanced medical services. The purpose of this study was to determine the impact of SEFT therapy on blood pressure in hypertensive elderly people at the Nakula Elderly Integrated Health Post (Posyandu). This study also aims to provide a scientific basis for developing a spiritual and emotional-based community intervention model to lower blood pressure in the elderly, while supporting a promotive-preventive approach in the primary health care system. Furthermore, it is important to understand that blood pressure in the elderly is influenced not only by physiological factors but also by psychological conditions such as stress, anxiety, and feelings of loneliness, which are common in old age.